Influence of Energy-Saving Systems Using Natural Cold on the Energy Intensity of the Milk Cooling Process - A. B. Korshunov (Сельскохозяйственные машины и технологии, 2020)
Reduction of energy consumption in technological processes of cooling and storage milk on farms is urgent task.(Research purpose) The research purpose is in reducing the energy intensity of the milk cooling process on farms while maintaining its quality.(Materials and methods) The authors conducted research to improve existing and create new smart combined cooling systems based on the rational use of natural and artificial cold sources with means of its accumulation and environmentally friendly coolants with low freezing point.(Results and discussion) The authors have found the dependence of the amount of energy that can be used for cooling and storage of milk and dispersed into the environment on the potential of natural cold of the area and the location of the technological object. The article presents a methodology for assessing the potential of natural cold for different regions of Russia. According to the methodology, authors calculated the values of the ice storage capacities for dairy farms with different livestock and annual milk yield. The article presents the diagram of electric energy savings when using natural cold to cooling milk on farms of 400 heads with a yield of 5000 liters in different climatic regions of Russia. Significant energy savings can be obtained through the use of combined accumulators of natural and artificial cold using environmentally friendly coolants with low freezing point and ground ice storage, in which the freezing of soil and water is carried out due to the ground cooling thermal installation with twophase thermosyphons.(Conclusions) The use of smart combined milk cooling systems on farms on the basis of sources of natural and artificial cold with means of its accumulation and environmentally friendly coolants with low freezing point allows to reduce energy consumption in 1.5-3 times at preservation of its quality. At the same time, such systems in various configurations can be effectively used in all agroclimatic regions of the country.